PBT-PC composite material and preparation method and application thereof

By controlling the specific by-products and residual monomer content in PBT and PC resins, PBT-PC composite materials with wide processing windows and excellent mechanical properties were prepared, which solved the problem of feedstock caused by transesterification reaction and improved the application performance of the material.

CN119775730AActive Publication Date: 2025-04-08KINGFA SCI & TECH CO LTD

Patent Information

Application Number
CN202411994031.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

During the alloying process of PBT and PC, transesterification reaction leads to frequent feedstock phenomena in injection molding, product performance declines, and processing windows are short.

Method used

By controlling the tetrahydrofuran content in the PBT resin and the residual content of bisphenol A in the PC resin, PBT-PC composite materials with specific properties were prepared to inhibit transesterification reactions and expand the processing window.

Benefits of technology

It realizes that the PBT-PC composite material still maintains good tensile strength after staying at high temperature, expands the processing window for alloying production, and improves the application performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005224221220000111
    Figure BDA0005224221220000111
  • Figure BDA0005224221220000121
    Figure BDA0005224221220000121
  • Figure BDA0005224221220000122
    Figure BDA0005224221220000122
Patent Text Reader

Abstract

The invention relates to a PBT-PC composite material as well as a preparation method and application thereof. The PBT-PC composite material comprises PBT resin, PC resin and a transesterification inhibitor, the content of tetrahydrofuran in the PBT resin is less than 1000 ppm; the content of bisphenol A in the PC resin is less than 100 ppm. According to the invention, the content of tetrahydrofuran in the PBT resin and the content of residual bisphenol A monomer in the PC resin are controlled, so that the PBT-PC composite material still has good tensile strength after staying at high temperature, and further has a wider processing window in alloying production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a PBT-PC composite material and a preparation method and application thereof. Background Art

[0002] Polycarbonate (PC) is a linear, almost colorless, glassy amorphous polymer with the advantages of good impact strength, excellent electrical insulation, wide operating temperature range and good product dimensional stability. It is one of the five major engineering plastics and an excellent thermoplastic engineering plastic, widely used in the fields of electronics, automobile industry, medical equipment, aerospace, etc. However, PC molecules contain a large number of benzene rings, with large molecular rigidity and steric hindrance, so their melting temperature is high, the flowability is poor during processing, the products are prone to stress cracking, the residual stress is large, the wear resistance is poor, and they are sensitive to notches, all of which limit their production applications.

[0003] Polybutylene terephthalate (PBT) is a polyester engineering plastic with excellent comprehensive performance, and has very good chemical stability, mechanical strength (such as toughness, fatigue resistance, self-lubrication, etc.), electrical insulation properties and thermal stability. It has a fast crystallization rate, can be formed at high speed, has excellent solvent resistance, heat resistance, toughness and wear resistance, and low water absorption. It still maintains various good properties in a humid environment and has good electrical insulation. However, its disadvantages are low notch impact strength and large molding shrinkage.

[0004] Therefore, blending and modifying PC and PBT can not only make up for the shortcomings of PC such as high melt viscosity, poor fluidity, and poor solvent resistance, but also improve the defects of PBT such as low impact resistance. For example, CN113956643A discloses a chemically resistant, scratch-resistant, high-hardness PC / PBT composite material and a preparation method thereof. The composite material comprises the following components by weight percentage: 50-70% polycarbonate, 20-40% polybutylene terephthalate, 3-5% compatibilizer, 4-6% toughening agent, 0.3-0.5% lubricant, 0.2-0.3% ester exchange promoter, and 0.2-0.4% compound antioxidant. The ester exchange promoter is a weakly alkaline metal oxide with a particle size greater than 8000 mesh. By adopting the ester exchange promoter, the ester exchange reaction of PC / PBT is accelerated and the interfacial compatibility of PC and PBT is improved. The addition of the ester exchange promoter can effectively improve the rigidity, toughness and pencil hardness of the material, and the addition of the compatibilizer and toughening agent can improve the toughness and heat resistance of the material. At the same time, a special high-hardness PC is used to improve the surface hardness of the PCPBT alloy and improve the scratch resistance of the alloy material.

[0005] However, during the alloying process, the ester exchange reaction between PBT and PC often leads to the problem of material flower and product performance degradation during the injection molding process, resulting in a short processing window for PBT and PC alloying. Therefore, it is urgent to develop a PBT-PC composite material with a wide processing window that can maintain excellent mechanical properties when staying at high temperature in the extruder. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a PBT-PC composite material and a preparation method and application thereof. By controlling the tetrahydrofuran content in the PBT resin and the residual bisphenol A monomer content in the PC resin, the PBT-PC composite material still has good tensile strength after being kept at high temperature, thereby having a wider processing window in alloying production.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a PBT-PC composite material, wherein the PBT-PC composite material comprises a PBT resin, a PC resin and an ester exchange inhibitor; the tetrahydrofuran (THF) content in the PBT resin is less than 1000 ppm; and the bisphenol A content in the PC resin is less than 100 ppm.

[0009] The PBT-PC composite material provided by the present invention limits the THF content in the PBT resin and the bisphenol A content in the PC resin, wherein THF is a byproduct in the production of the PBT resin, and bisphenol A is a raw material monomer of the PC resin, which remains in the PC resin due to incomplete reaction, and the contents of both have a significant impact on the product performance. The present invention uses a PBT resin with a THF content of less than 1000ppm and a PC resin with a bisphenol A content of less than 100ppm for compounding, so that the tensile strength of the composite material after staying at high temperature is still excellent, has a wide processing window, and the prepared PBT-PC composite material has good application performance.

[0010] The tetrahydrofuran content in the PBT resin is less than 1000ppm, for example, it can be 950ppm, 900ppm, 850ppm, 800ppm, 750ppm, 700ppm, 650ppm, 600ppm, 550ppm, 500ppm, 450ppm, 400ppm, 350ppm, 300ppm, 250ppm, 200ppm, 150ppm, 100ppm, 50ppm, 30ppm, 10ppm, 5ppm, 1ppm, and specific point values ​​between the above point values. Due to space limitations and for simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range. Based on purification cost considerations, the tetrahydrofuran content in the PBT resin is greater than 10ppm, and it is further preferred that the tetrahydrofuran content is 10 to 900ppm, more preferably 100 to 600ppm, and more preferably 200 to 500ppm.

[0011] In the present invention, the PBT resin with a specific tetrahydrofuran content can be purchased from the market or prepared by a conventional method. Exemplarily, the method comprises: adding a commercially available PBT resin with a high tetrahydrofuran content to a solid phase device, and keeping it at 180 to 200° C. for 5 to 8 hours. By changing the temperature and time, PBT resins with different tetrahydrofuran contents can be obtained.

[0012] In the present invention, the tetrahydrofuran content in the PBT resin is tested by a static headspace method, and the specific testing method is as follows:

[0013] (1) Preparation of THF standard curve

[0014] THF methanol solutions with concentrations of 0.010 g / L, 0.1 g / L, 1.0 g / L, 5.0 g / L, 10.0 g / L, 20.0 g / L, 50.0 g / L and 100.0 g / L were prepared, and the peak areas of THF in the THF methanol solutions with different concentrations were tested by the static headspace method. A standard curve of THF was prepared with the peak area of ​​THF as the ordinate and the concentration of THF as the abscissa.

[0015] (2) Determination of THF content in PBT resin:

[0016] Accurately weigh about 1.2000g of the sample to be tested and add it to a static headspace test bottle. The peak area of ​​THF in the PBT resin is tested by the static headspace method. The content of THF in the sample to be tested can be calculated based on the peak area of ​​THF in the PBT resin and the THF standard curve. The standard curve is calibrated by tetrahydrofuran / methanol solution.

[0017] Among them, the static headspace test conditions are as follows:

[0018] Temperature: Heating box: 105°C; Quantitative loop: 135°C; Transfer line: 165°C.

[0019] Time: Vial equilibration: 120 min; Injection duration: 0.09 min; GC cycle: 30 min.

[0020] The instrument model and parameters used for static headspace are as follows: Agilent Technologies 7697 Headspace Sampler; Agilent Technologies 7890 AGC System; chromatographic column: J&W 122-7032: 250 °C: 30m×250μm×0.25μm; injection: front SS inlet N2; sample output: front detector FID.

[0021] The bisphenol A content in the PC resin is less than 100ppm, for example, it can be 95ppm, 90ppm, 85ppm, 80ppm, 70ppm, 60ppm, 50ppm, 40ppm, 30ppm, 20ppm, 15ppm, 10ppm, 5ppm, 1ppm, and specific point values ​​between the above point values. Due to space limitations and for simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range. Based on purification cost considerations, the bisphenol A content in the PC resin is greater than 1ppm, more preferably the bisphenol A content is 1 to 90ppm, and particularly preferably the bisphenol A content is 10 to 60ppm.

[0022] In the present invention, the PC resin with a specific content of bisphenol A can be purchased from the market or prepared by conventional methods; illustratively, the method comprises: placing a PC resin with a high bisphenol A content in a twin-screw extruder, extruding at a temperature of 220 to 300° C. and a vacuum degree of -0.05 to -0.1 MPa, and by changing the temperature and vacuum degree, PC resins with different bisphenol A contents can be obtained.

[0023] In the present invention, the bisphenol A content in the PC resin is tested by high performance liquid chromatography, and the specific testing method is as follows:

[0024] The content of BPA is determined by high performance liquid chromatography, and the instrument conditions and methods are as follows: high performance liquid chromatograph (with fluorescence detector); excitation wavelength is 227nm; emission wavelength is 313nm; chromatographic conditions are: total flow rate 1mL / min, column oven 40°C, retention time 9.2min, mobile phase A is methanol, mobile phase B is water; gradient elution is 0-8min, 70% A; 8-10min, 80% A; 10-12min, 90% A; 12-13min, 100% A. Preferably, the tetrahydrofuran content in the PBT resin is 11-999ppm.

[0025] Preferably, in parts by weight, the PBT-PC composite material comprises 8-55 parts of PBT resin, 8-55 parts of PC resin and 0.05-1 part of ester exchange inhibitor.

[0026] Preferably, the PBT-PC composite material comprises, by weight, 15-55 parts of PBT resin, 15-55 parts of PC resin, and 0.05-1 parts of ester exchange inhibitor.

[0027] The PBT resin is 8-55 parts, for example, it can be 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts or 50 parts, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0028] The PC resin is 8-55 parts, for example, it can be 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts or 50 parts, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0029] The ester exchange inhibitor is 0.05-1 part, for example, it can be 0.1 part, 0.2 part, 0.3 part, 0.5 part, 0.6 part or 0.8 part, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0030] The “parts” and “parts by weight” involved in the present invention are all calculated based on solid content and do not include solvents, dispersants, etc.

[0031] The present invention adopts a specific content of the ester exchange inhibitor to be compounded with other components, which can effectively control the ester exchange reaction between PBT and PC, and solves the problem of material flower and product performance degradation during the injection molding process.

[0032] Preferably, the mass ratio of the PBT resin to the PC resin is 1:(0.1-6.2), for example, it can be 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.8, 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2, 1:2.2, 1:2.5, 1:3, 1:4, 1:4.5, 1:5 or 1:5.5, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and more preferably 1:(0.3-3).

[0033] The present invention adopts a specific ratio of PBT resin and PC resin, so that the prepared PBT-PC composite material has a wider processing window and significantly improved strength, which can meet the performance requirements of more fields and expand its application space.

[0034] Preferably, the intrinsic viscosity of the PBT resin is greater than 0.8 dl / g, for example, it may be 0.9 dl / g, 1.0 dl / g, 1.1 dl / g, 1.2 dl / g, 1.3 dl / g, 1.4 dl / g, 1.5 dl / g, 1.8 dl / g or 2 dl / g, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0035] The intrinsic viscosity in the present invention is measured at 23° C. in accordance with the standard “GB / T 1632-1993 Determination of viscosity and intrinsic viscosity of dilute polymer solutions”.

[0036] Preferably, the melt index of the PC resin measured at 300°C / 1.2kg is ≤25g / 10min, for example, it may be 22g / 10min, 20g / 10min, 15g / 10min, 10g / 10min, 9.5g / 10min, 9g / 10min, 8g / 10min, 7g / 10min, 6g / 10min or 5g / 10min, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and it is further preferably ≤10g / 10min.

[0037] In the present invention, the melt index is measured using a melt index tester according to ASTM D1238-2010 standard under the condition of 300° C. / 1.2 kg.

[0038] Preferably, the transesterification inhibitor includes any one of zinc dihydrogen phosphate, sodium dihydrogen phosphate or zinc hydrogen phosphate, or a combination of at least two thereof.

[0039] Preferably, the PBT-PC composite material further comprises an auxiliary agent.

[0040] Preferably, the auxiliary agent includes any one of a flame retardant, a synergistic flame retardant or a toughening agent, or a combination of at least two thereof.

[0041] Preferably, the weight proportion of the flame retardant is 8-15 parts, for example, it can be 9 parts, 10 parts, 11 parts, 12 parts, 13 parts or 14 parts, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0042] Preferably, the flame retardant includes any one of a brominated flame retardant, a sulfonate flame retardant or a phosphorus flame retardant, or a combination of at least two thereof.

[0043] Preferably, the brominated flame retardant includes any one of brominated polycarbonate, brominated epoxy, polybrominated styrene, tetrabromobisphenol A, decabromodiphenyl ether, polydibromophenyl ether or tetradecabromodiphenoxybenzene, or a combination of at least two thereof.

[0044] Preferably, the sulfonate flame retardant is any one of potassium perfluorobutylsulfonate, potassium benzenesulfonylbenzenesulfonate or sodium 2,4,5-trichlorobenzenesulfonate, or a combination of at least two thereof.

[0045] Preferably, the phosphorus-based flame retardant includes any one of aluminum hypophosphite, diethyl aluminum hypophosphite, melamine polyphosphate, red phosphorus, ammonium polyphosphate, diammonium phosphate, triphenyl phosphate, tricresyl phosphate, tris(dibromopropyl) phosphate or tris(β-chloroethyl) phosphate, or a combination of at least two thereof.

[0046] Preferably, the weight proportion of the synergistic flame retardant is 1-5 parts, for example, it can be 1.5 parts, 2 parts, 3 parts, 4 parts or 4.5 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0047] Preferably, the synergistic flame retardant includes a silane flame retardant and / or an antimony flame retardant.

[0048] Preferably, the silane flame retardant includes any one of polysilane, polysiloxane or polyorganosilsesquioxane, or a combination of at least two thereof.

[0049] Preferably, the antimony-based flame retardant includes any one of antimony trioxide, colloidal antimony pentoxide or sodium antimonate, or a combination of at least two of them.

[0050] Preferably, the weight proportion of the toughening agent is 3-15 parts, for example, 4 parts, 5 parts, 6 parts, 8 parts, 10 parts, 12 parts or 14 parts, as well as specific values ​​between the above-mentioned points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0051] Preferably, the toughening agent includes any one of ethylene-acrylate-glycidyl methacrylate copolymer, ethylene-acrylate copolymer, ethylene-vinyl acetate copolymer, methacrylate-styrene-silicone copolymer, and methacrylate-styrene-butadiene copolymer, or a combination of at least two thereof.

[0052] The PBT-PC composite material provided by the present invention can be added with other additives according to actual needs. The other additives include any one of an antioxidant, a release agent, and an anti-drip agent, or a combination of at least two thereof.

[0053] Preferably, the antioxidant comprises a hindered phenol antioxidant and / or a phosphite antioxidant.

[0054] Preferably, the release agent includes any one of metal stearates, alkyl stearates, pentaerythritol stearates, paraffin wax, and montan wax, or a combination of at least two of them.

[0055] Preferably, the anti-drip agent includes a polytetrafluoroethylene anti-drip agent.

[0056] In a second aspect, the present invention provides a method for preparing the PBT-PC composite material as described in the first aspect, the preparation method comprising the following steps:

[0057] The PBT resin, PC resin, ester exchange inhibitor and optional auxiliary agents are mixed, extruded and granulated to obtain the PBT-PC composite material.

[0058] Preferably, the extrusion is carried out in a twin-screw extruder.

[0059] Preferably, the extrusion temperature is 150-300°C, for example, it can be 160°C, 170°C, 180°C, 200°C, 220°C, 250°C or 280°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0060] In a third aspect, the present invention provides an application of the PBT-PC composite material as described in the first aspect in electrical and electronic industries, automotive industry, medical equipment or aerospace.

[0061] In the present invention, the application in electrical and electronic, automotive industry, medical equipment or aerospace is used, for example, in photovoltaic connectors, energy storage connectors, charging guns for new energy batteries, housings for disinfection guns, and housings for power tool battery packs.

[0062] Compared with the prior art, the present invention has at least the following beneficial effects:

[0063] The invention provides a PBT-PC composite material, comprising a PBT resin, a PC resin, a flame retardant, a synergistic flame retardant, a toughening agent and an ester exchange inhibitor. The PBT resin with a specific tetrahydrofuran content and the PC resin with a specific residual bisphenol A monomer content are compounded with other components, so that the tensile strength retention rate of the PBT-PC composite material after staying at 270°C for 10 minutes is above 80%, and the PBT-PC composite material has a wide processing window of 230-300°C in alloying production. DETAILED DESCRIPTION

[0064] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0065] In the following specific implementation of the present invention, the materials involved are as follows:

[0066] 1) PBT resin

[0067] PBT-1: Tetrahydrofuran content 875 ppm, intrinsic viscosity 0.86 dl / g, obtained by feeding PBT-TH6082 into a solid phase device and keeping it at 180°C for 5 hours.

[0068] PBT-2: tetrahydrofuran content 490 ppm, intrinsic viscosity 0.88 dl / g; PBT-1 was fed into a solid phase device and retained at 185°C for 5.5 hours to obtain.

[0069] PBT-3: The tetrahydrofuran content is 385 ppm and the intrinsic viscosity is 0.89 dl / g; PBT-1 is fed into a solid phase device and retained at 185°C for 6 hours to obtain.

[0070] PBT-4: The tetrahydrofuran content is 235 ppm and the intrinsic viscosity is 0.91 dl / g; PBT-1 is fed into a solid phase device and retained at 190°C for 6.5 hours to obtain.

[0071] PBT-5: The tetrahydrofuran content is 110 ppm and the intrinsic viscosity is 0.92 dl / g; PBT-1 is fed into a solid phase device and retained at 195°C for 6.5 hours to obtain.

[0072] PBT-6: The tetrahydrofuran content is 30 ppm and the intrinsic viscosity is 0.95 dl / g; PBT-1 is fed into a solid phase device and kept at 200°C for 7 hours to obtain it.

[0073] PBT-7: The tetrahydrofuran content is 380 ppm and the intrinsic viscosity is 1.28 dl / g; PBT-GL236 (purchased from Yizheng Chemical Fiber Co., Ltd.) is fed into a solid phase device and kept at 180° C. for 5 hours to obtain.

[0074] PBT-d1: PBT-TH6082, purchased from Tunhe, Lanshan, Xinjiang, with a tetrahydrofuran content of 1124 ppm and an intrinsic viscosity of 0.83 dl / g.

[0075] 2) PC resin

[0076] PC-d1: Bisphenol A content 120ppm, melt index 8.5g / 10min, LXZY1809-01H, purchased from Liaocheng Luxi Polycarbonate Co., Ltd.

[0077] PC-1: Bisphenol A content 72ppm, melt index 8.0g / 10min; PC-d1 is added into a twin-screw extruder and extruded at an extrusion temperature of 250°C and a vacuum degree of -0.06MPa.

[0078] PC-2: Bisphenol A content 30ppm, melt index 6.2g / 10min; PC-d1 was added into a twin-screw extruder and extruded at an extrusion temperature of 280°C and a vacuum degree of -0.08MPa.

[0079] PC-3: Bisphenol A content 6ppm, melt index 5.2g / 10min; PC-d1 is added into a twin-screw extruder and extruded at an extrusion temperature of 300°C and a vacuum degree of -0.1MPa.

[0080] PC-4: Bisphenol A content 8ppm, melt index 20g / 10min, PC1300 22NP (purchased from LG Chem, Ltd.) was added into a twin-screw extruder and extruded at an extrusion temperature of 240°C and a vacuum degree of -0.05MPa.

[0081] 3) Toughening agent

[0082] Ethylene-acrylate copolymer, 1400PN, purchased from Shanghai Zhuangjing Chemical Co., Ltd.

[0083] SOG-003 was purchased from Jiayirong Polymer (Shanghai) Co., Ltd.

[0084] 4) Flame retardant

[0085] Brominated epoxy flame retardant: F-2100, purchased from Bromine Compounds Ltd.

[0086] Brominated polycarbonate flame retardant: FG-8500, purchased from Guangdong Pushi Trading Co., Ltd.

[0087] 5) Synergistic flame retardants

[0088] Antimony white: S-04N, purchased from Yiyang Shengli Materials Technology Co., Ltd.

[0089] Examples 1-17, Comparative Examples 1-3

[0090] A PBT-PC composite material, the types and amounts of each component are shown in Table 1 and Table 2, and the amount unit of each component is "part";

[0091] The PBT-PC composite material is prepared by the following method:

[0092] PBT resin, PC resin, flame retardant, synergistic flame retardant, toughening agent and transesterification inhibitor were mixed according to the proportions in Table 1 and Table 2, and then put into a twin-screw extruder, extruded at 250° C., and granulated to obtain the PBT-PC composite material, which was used to test the original tensile strength and notched impact strength;

[0093] PBT resin, PC resin, flame retardant, synergistic flame retardant, toughening agent and ester exchange inhibitor were mixed according to the proportions in Table 1 and Table 2 and put into a twin-screw extruder. After staying at 270° C. for 10 minutes, they were extruded and granulated to obtain the PBT-PC composite material, which was used to test the tensile strength after staying at 270° C. for 10 minutes.

[0094] The PBT-PC composite materials in the examples or comparative examples were tested as follows:

[0095] 1) Tensile strength:

[0096] The test was carried out in accordance with the method specified in GB / T 1040.2-2022 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics", and the test speed was 10 mm / min.

[0097] 2) Izod notched impact strength

[0098] The Izod notched impact strength is tested according to ISO 180 standard.

[0099] The test results are shown in Table 1 and Table 2.

[0100] Table 1

[0101]

[0102]

[0103] Table 2

[0104]

[0105]

[0106] It can be seen from the test results that the PBT-PC composite material provided by the present invention adopts a PBT resin with a specific tetrahydrofuran content and a PC resin with a specific residual bisphenol A monomer content, and is compounded with other components, so that the tensile strength retention rate of the PBT-PC composite material at 270° C. for 10 minutes is above 80%, and has a wide processing window in alloying production.

[0107] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A PBT-PC composite material, characterized in that: The PBT-PC composite material comprises PBT resin, PC resin and an ester exchange inhibitor; The tetrahydrofuran content in the PBT resin is less than 1000ppm; The content of bisphenol A in the PC resin is less than 100 ppm.

2. The PBT-PC composite material according to claim 1, characterized in that In parts by weight, the PBT-PC composite material comprises 8-55 parts of PBT resin, 8-55 parts of PC resin and 0.05-1 part of ester exchange inhibitor; Preferably, the PBT-PC composite material comprises, by weight, 15-55 parts of PBT resin, 15-55 parts of PC resin and 0.05-1 parts of ester exchange inhibitor; Preferably, the mass ratio of the PBT resin to the PC resin is 1:(0.1-6.2), more preferably 1:(0.3-3).

3. The PBT-PC composite material according to claim 1, characterized in that The tetrahydrofuran content of the PBT resin is 10 to 900 ppm, preferably 100 to 600 ppm, and more preferably 200 to 500 ppm.

4. The PBT-PC composite material according to claim 1, characterized in that The bisphenol A content in the PC resin is 1 to 90 ppm, preferably 10 to 60 ppm.

5. The PBT-PC composite material according to claim 1, characterized in that The transesterification inhibitor includes any one of zinc dihydrogen phosphate, sodium dihydrogen phosphate or zinc hydrogen phosphate, or a combination of at least two thereof.

6. The PBT-PC composite material according to claim 1, characterized in that: The PBT-PC composite material also includes an additive; Preferably, the auxiliary agent includes any one of a flame retardant, a synergistic flame retardant or a toughening agent, or a combination of at least two thereof.

7. The PBT-PC composite material according to claim 6, characterized in that: The weight portion of the flame retardant is 8-15 parts; Preferably, the flame retardant includes any one or a combination of at least two of a brominated flame retardant, a sulfonate flame retardant or a phosphorus flame retardant; Preferably, the brominated flame retardant includes any one or a combination of at least two of brominated polycarbonate, brominated epoxy, polybrominated styrene, tetrabromobisphenol A, decabromodiphenyl ether, polydibromophenyl ether or tetradecabromodiphenoxybenzene; Preferably, the sulfonate flame retardant is any one of potassium perfluorobutyl sulfonate, potassium benzenesulfonylbenzenesulfonate or sodium 2,4,5-trichlorobenzenesulfonate, or a combination of at least two thereof; Preferably, the phosphorus-based flame retardant includes any one of aluminum hypophosphite, diethyl aluminum hypophosphite, melamine polyphosphate, red phosphorus, ammonium polyphosphate, diammonium phosphate, triphenyl phosphate, tricresyl phosphate, tris(dibromopropyl) phosphate or tris(β-chloroethyl) phosphate, or a combination of at least two thereof; Preferably, the weight portion of the synergistic flame retardant is 1-5 parts; Preferably, the synergistic flame retardant includes a silane flame retardant and / or an antimony flame retardant; Preferably, the silane flame retardant includes any one or a combination of at least two of polysilane, polysiloxane or polyorganosilicon silsesquioxane; Preferably, the antimony-based flame retardant includes any one or a combination of at least two of antimony trioxide, colloidal antimony pentoxide or sodium antimonate; Preferably, the weight portion of the toughening agent is 3-15 parts; Preferably, the toughening agent includes any one of ethylene-acrylate-glycidyl methacrylate copolymer, ethylene-acrylate copolymer, ethylene-vinyl acetate copolymer, methacrylate-styrene-silicone copolymer, and methacrylate-styrene-butadiene copolymer, or a combination of at least two thereof.

8. A method for preparing the PBT-PC composite material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The PBT resin, PC resin, ester exchange inhibitor and optional auxiliary agents are mixed, extruded and granulated to obtain the PBT-PC composite material.

9. The preparation method according to claim 8, characterized in that: The extrusion is carried out in a twin-screw extruder; Preferably, the extrusion temperature is 150-300°C.

10. Use of the PBT-PC composite material according to any one of claims 1 to 7 in electrical and electronic industries, automobile industry, medical equipment or aerospace.

Citation Information

Patent Citations

  • Chemical-resistant scratch-resistant high-hardness PCPBT composite material and preparation method thereof

    CN113956643A

  • Pc / abs compositions with good thermal and chemical stability

    CN104254570A

  • PC / PBT alloy and product thereof

    CN108342056A

  • Glass fiber reinforced ASA / PBT alloy material and preparation method and application thereof

    CN113956598A

  • Polybutylene terephthalate resin and molded article

    JP2003012781A

Cited By

  • PBT-PC composite material, preparation method therefor, and use thereof

    WO2026145248A1